Hsa-mir-125b-2 is highly expressed in childhood ETV6/RUNX1 (TEL/AML1) leukemias and confers survival advantage to growth inhibitory signals independent of p53 - Gefen, Nir (2009)
MicroRNAs (miRNAs) regulate the expression of multiple proteins in a dose dependent manner. We hypothesized that increased expression of miRNAs encoded on chromosome 21 (chr 21) contribute to the leukemogenic role of trisomy 21. The levels of chr 21 miRNAs were quantified by qRT-PCR in four types of childhood ALL characterized by either numerical (trisomy or tetrasomy) or structural abnormalities of chr 21. Suprisingly high expression of the hsa-mir-125b-2 cluster, consisting of three miRNAs, was identified in leukemias with the structural ETV6/RUNX1 abnormality and not in ALLs with trisomy 21. Manipulation of ETV6/RUNX1 expression and chromatin immunoprecipitation studies demonstrated that the high expression of the miRNA cluster is an event independent of the ETV6/RUNX1 fusion protein. Overexpression of hsa-mir-125b-2 conferred a survival advantage to Ba/F3 cells following IL-3 withdrawal or a broad spectrum of apoptotic stimuli through inhibition of caspase 3 activation. Conversely, knockdown of the endogenous miR-125b in the ETV6/RUNX1 leukemia cell line REH increased apoptosis after Doxorubicin and Staurosporine treatments. P53 protein levels were not altered by miR-125b. Together these results suggest that the expression of hsa-mir-125b-2 in ETV6/RUNX1 ALL provides survival advantage to growth inhibitory signals in a p53 independent manner.